Pengaruh Powder Cangkang Gonggong Dengan Aktivasi Fisika Terhadap Limbah Cair Pembuatan Tahu - Rizki, Bagas; Darta, Yuli; Sugiyarto, Sugiyarto; Wahyudie, Ilham Ary (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Tofu manufacturing wastewater produces water that contains low pH. The wastewater is flowed into the river so that the water is polluted and becomes acidic. To increase the pH of the polluted water, adsorbents have been made from Laevistrombus Canarium. Laevistrombus Canarium can be utilized as adsorbents by activation. Activation is useful to increase the adsorption charge, so that the adsorption energy can be increased. The activation process is carried out using an oven with temperatures of 550 ° C, 650 ° C, and 750 ° C. The powder used is mesh 100, 150, and 200. Activated Laevistrombus Canarium powder can increase the pH of water. The results showed that snail powder can increase the pH of water polluted by tofu-making wastewater. By using the Taguchi method, the activation temperature of the adsorbent showed the optimal value at a temperature of 550°C and a powder size of 100 (149m).